A Study on L-Asparaginase of Nocardia levis MK-VL_113 - Kavitha, Alapati (The Scientific World Journal, 2012)
An enzyme-based drug, L-asparaginase, was produced by Nocardia levis MK-VL_113 isolated from laterite soils of Guntur region. Cultural parameters affecting the production of L-asparaginase by the strain were optimized. Maximal yields of L-asparaginase were recorded from 3-day-old culture grown in modified asparagine-glycerol salts broth with initial pH 7.0 at temperature 30°C. Glycerol (2%) and yeast extract (1.5%) served as good carbon and nitrogen sources for L-asparaginase production, respectively. Cell-disrupting agents like EDTA slightly enhanced the productivity of L-asparaginase. Ours is the first paper on the production of L-asparaginase by N. levis.